Association Between Cancer-Related Fatigue and Falls in Patients With Myeloproliferative Neoplasms: Results of a Multicenter Cross-Sectional Survey From the East German Study Group for Hematology and Oncology (OSHO #97) - Sabine Felser PhD; Martin Gube MEd; Julia Gruen; Philipp Ie Coutre MD; Susann Schulze MD; Lars-Olof Muegge MD; Christian Junghanss MD; Sabina Ulbricht PhD (Integrative Cancer Therapies, 2022)
Objective: This study retrospectively examined the association between cancer-related fatigue (CrF) and the number of falls during the last 12 months in patients with myeloproliferative neoplasms (MPNs). Methods: A multicenter, 1-time anonymous survey was conducted using analog and digital questionnaires. Sex-stratified multinomial logistic regression analysis was applied to investigate the association between CrF and number of falls. All analyses were adjusted for age, school education, body mass index, MPN subtype, and quality of life. Results: The final sample comprised 688 patients (mean age 57.4 ± 13.8, 62.4% women). The fall rate was 16.2% in women and 12.2% in men ( P  = .153). There were no differences between women and men in terms of CrF between individuals with more than 1 fall, whereas women with 1 fall had a higher CrF compared to those without a fall (RRR = 1.019; 95% CI [1.002-1.039]), respectively. Conclusion: CrF increases the risk of falls in women with MPN. Physicians should evaluate and manage CrF symptoms and implement fall prevention strategies for those who are at increased risk. Further research is needed to better understand the effects of CrF on gait performance and associated fall risk.